THE POTENTIAL OF YOUNG ENTREPRENEURS INDEPENDENCE TO TECHNOPRENEURSHIP IN THE DIGITAL AGE - Hastuti Hastuti (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
Technical progress has a huge influence on a country's global competitiveness in the modern era. The purpose of this study was to determine whether or not young entrepreneurs can be technologically self-sufficient in the digital age. The application of cutting-edge appropriate technology in company development, along with a well-established entrepreneurial spirit, will be able to maximize both the process and the outputs of the newly formed business unit. This is what technopreneurship is all about: a collaboration between the use of technology as a tool and the desire to work for yourself. This research seeks to explore the description of the business process (entrepreneur) using a technical basis from an educational viewpoint (technopreneurship). According to the abstract, this study will provide an overview of how entrepreneurs and small and medium businesses use technology. Teknopreneurship is the next step in the evolution of entrepreneurship. This study is expected to be a benchmark for the progress of the independence of young entrepreneurs. conceptual research that illustrates the importance of the independence of young entrepreneurs in introducing technopreneurship in the digital era by using secondary data from publications related to the research theme.